ISLAM DAN FUNDAMENTALISME DALAM AL-QURAN - Azhar Nur aziz; Albi Al-Bukhari; Azhar Nur Aziz Syihabudin (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
The phenomenon of terrorism and religiously motivated violence that has spread almost all over the world, especially in the Islamic world, from Egypt and other Middle Eastern countries to Indonesia, has shocked many people today. For example, when the terrorist act that occurred at the United States World Trade Center (WTC) building killed nearly three thousand people, this incident became a discourse on the reemergence of fundamentalism which had faded. As a socio-religious symptom, fundamentalism is very influential on other religions which they consider to have undermined the glories of religion in the past. The fundamental issue that all Muslims must examine is whether they want to live in a world with other people or whether they prefer to live in their own purely Islamic universe, Muslims who turn a blind eye to the events taking place in many worlds actually create home to themselves in exile.